Structural evolution of the Rieserferner pluton in the framework of the Oligo-Miocene tectonics of the Eastern Alps. (November 2018) - Ceccato, Alberto; Pennacchioni, Giorgio
Abstract: The structural evolution of the Oligocene Rieserferner pluton (Eastern Alps), developed during pluton cooling and exhumation, includes localized deformation structures consisting of: (i) steeply dipping joints, leucocratic dykes and quartz-feldspar veins, and related ductile shear zones (formed at ∼600 °C); (ii) shallowly dipping joints with associated epidote and quartz veins, and related ductile shear zones (∼450 °C); (iii) steeply dipping mafic dykes and calcite + white mica-bearing brittle-ductile faults (∼300 °C); (iv) steeply dipping pseudotachylyte-bearing faults (<250 °C); and (v) zeolite-bearing faults (<200 °C). The structures (i-iii) and (iv-v) can be dated to the Oligocene and Early Miocene, respectively. The kinematic analysis suggests a change in local shortening direction from N290° to N350°, interpreted to reflect a change from transtension in the Early Oligocene, associated with a N060°-directed plate divergence, to transpression in the Miocene, associated with a (N)NW-directed plate convergence. This evolution reflects the sequence of transient and long-term geodynamic processes occurring in the Eastern Alps during the Tertiary, including slab break-off of the subducted European slab, the indentation of the Dolomites promontory against the Alpine stack of nappes, and the exhumation and lateral escape tectonics of the Alpine belt. Highlights: A sequence of solid-state ductile and brittle structures occurs in the Rieserferner. The local shortening direction switched from E-W to N-S during Oligocene. The switch reflects transition from transtension to transpression during Oligocene. Transient transtension occurred during pluton intrusion and early stages of cooling. E-dipping normal shear zones suggest incipient Early-Oligocene extension.